Bone Marrow Aspirate Clot: A Useful Technique in Diagnosis and Follow-Up of Hematological Disorders - Cantadori, Lucas Oliveira [UNESP]; Gaiolla, Rafael Dezen [UNESP]; Niero-Melo, Ligia [UNESP]; Oliveira, Cristiano Claudino [UNESP] (Hindawi Ltd, 2019)
Bone marrow biopsy is a diagnostic tool largely used in the evaluation of a broad number of disorders that could affect the hematopoietic system. Differently, bone marrow aspirate clot technique is rarely performed even though it has been described in literature. Here, we highlight the utility of the bone marrow aspirate clot, exemplifying through the discussion of three clinical cases in which this technique was used for diagnosis and follow-up purposes: megaloblastic hemopathy, multiple myeloma, and chronic lymphocytic leukemia. Bone marrow clot analysis increases sensitivity to diagnose hemopathies and offers the possibility of morphological evaluation and anatomopathological study, with the advantage of not needing decalcification processes, hence improving antigenic expression in immunohistochemical and FISH techniques. It is an easy-to-perform technique, offering a quick, reliable, and more comfortable procedure for patients.